1989
DOI: 10.1093/clinchem/35.9.1901
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the "cystic fibrosis protein" from serum.

Abstract: "Cystic fibrosis protein" (CFP), a minor serum protein marker of the cystic fibrosis allele, was isolated from serum from patients with cystic fibrosis by use of the "FPLC" high-resolution chromatography system and preparative sodium dodecyl sulfate-polyacrylamide gel electrophoresis. CFP currently is characterized by its isoelectric point (8.4) on isoelectric focusing. However, after the first purification steps, we identified the protein, which was present in a very low concentration, by the immunosorbent as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…During chronic inflammatory conditions, including that underlying CF lung disease, S100A8 and S100A9 are coordinately upregulated and secreted into the extracellular milieu [ 57 , 81 ], and their products elevated in the serum of patients [ 82 - 87 ], (reviewed in [ 50 ]). Likewise, coordinate regulation of S100A8 and S100A9 is also observed in neutrophils where absence of S100A9 leads to a coordinate loss of S100A8 expression [ 60 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…During chronic inflammatory conditions, including that underlying CF lung disease, S100A8 and S100A9 are coordinately upregulated and secreted into the extracellular milieu [ 57 , 81 ], and their products elevated in the serum of patients [ 82 - 87 ], (reviewed in [ 50 ]). Likewise, coordinate regulation of S100A8 and S100A9 is also observed in neutrophils where absence of S100A9 leads to a coordinate loss of S100A8 expression [ 60 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRP14 and MPR8 have been found in serum in pathological cases (Briiggcn et Kuruto et al, 1990; Barthe et al, 1991), and it has been suggested that these proteins could be secreted from phagocytic cells (Hedgeworth et al, 1991). It was interesting to test whether they could be released from bovine neutrophils by exocytosis upon addition of stimulating ligands.…”
Section: Resultsmentioning
confidence: 99%